Community perceptions and willingness to participate in COVID-19 vaccine trials: a qualitative study in Northern Ghana - Chatio, Samuel Tamti; Ansah, Nana Akosua; Nonterah, Engelbert A.; Bangre, Oscar; Awuni, Denis; Kuwolamo, Irene; Asoala, Victor; Ansah, Patrick (International Journal of Clinical Trials, 2024)
Background: Several COVID-19 vaccines were developed and are being tested to find effective vaccine to control the COVID-19 pandemic. The Navrongo health research centre was engaged to conduct trials on the safety and efficacy of some of the COVID-19 vaccines to inform policy in Ghana. This study explored perceptions and willingness to participate in the COVID-19 vaccine trials that were conducted in the Kassena-Nankana districts of Northen Ghana. Methods: This study used qualitative research approach where 10 focus group discussions and 30 in-depth interviews were conducted with participants. The data were coded into themes using QSR NVivo 12 software before thematic analysis. Results: The majority of participants perceived that the COVID-19 vaccine trial was a good initiative, which had helped people to get access to the vaccines to boost their immunity against the virus. However, some participants felt that it was not appropriate for NHRC to conduct the trials because of the perceived risks associated with the vaccines. Most participants said they were ready to participate in the trials if they were invited with many of them mentioning good health and compensation as the main factors that could influence their decision. Nonetheless, a good number of them maintained that they were not ready to participate because of perceived risks resulting from receiving the COVID-19 vaccines. Conclusion: Our recommendation is that effective community engagement strategies by researchers such as collaborating with key community leaders, to actively get involved during community education prior to conducting clinical trials, could improve understanding and participation.